Impact of Remote Working Environment in Kenyan Organizations - Otunga, Omollo Emily; Onyango Aila, Fredrick (My University, 2022)
A remote working environment refers to working outside the traditional workspace. Such environments define working as a mobile activity rather than needing a specific space to accomplish it. Remote work has been around for some time before the pandemic however, the quarantine and lockdown protocols pushed many organizations to adopt the system. Other organizations have found the conveniences of remote working, including reduced rental expenses and other organizational amenities while maintaining profitability and productivity. The remote working environment is here to stay in the professional realm; hence this seminar paper seeks to look at organizations in Kenya. Most sectors in Kenya were adversely affected by the remote working environment. The study adopted the review and analysis methodology of the existing literature, through the Google Scholar search engine and Z- library by use of keywords to investigate the impact of remote working environments on employee productivity, attitudes, and challenges to Kenyan organizations. The paper also looks at the overall organizational performance in a remote working environment. The study reveals that employee performance and attitude are significantly boosted in the remote working environment. Distractions and lack of proper utilities were highlighted as the key challenges faced by employees in remote working environments. The study also recommends the formulation of policies and procedures that will guide employees while choosing a framework for evaluating performance in the remote working environment.
Keywords: Remote Working Environment; Employee Challenges; Organizational Performance